Factors associated with unfavourable outcomes in COVID-19 patients with acute kidney injury: A single centre retrospective observational study - RAMESH, MIDHUN; VANNARATTA, ANASWARA; Pramod, Sarang; Naseeha, Fathima; Vellali, Rashidha; Ashok, Anesh; Pathirammal Agadi Purayil, Amjed (African Journal of Nephrology, 2022)
Background: COVID-19 infection adversely affects all nephron segments to cause acute kidney injury (AKI), leading to greater mortality. Methods: A retrospective analysis was conducted of patients (age >18 years) with COVID-19-related AKI admitted at a quaternary-level multispeciality hospital between September 2020 and April 2021. Data regarding various clinical, radiological, biochemical and haematological parameters were analysed and their association with clinical outcomes concerning mortality or survival was determined. Results: We included 67 patients (46 males) with a mean age of 68.2 ± 12.17 years, of whom 45 patients were haemodynamically unstable, and 52 had hypoxaemia at the time of presentation. Overall, 53% of the cases were discharged from the hospital and 46% succumbed to the illness; females had higher mortality (67%, P = 0.024). The mean neutrophil/lymphocyte ratio (P = 0.014), HbA1c (P = 0.011), LDH (P = 0.002), D-dimer (P = 0.034) and C-reactive protein (P = 0.001) levels at admission were higher in patients with unfavourable outcomes. Increased mortality was present in patients who had a higher clinical category of illness (P = 0.014), advanced AKI stage (P = 0.001), haemodynamic instability at presentation (P < 0.001), required some form of KRT (P = 0.009), oxygen (P = 0.047), ventilatory (P = 0.028) or inotropic support (P = <0.001), were on calcium channel blockers at the time of admission (P = 0.024) or required antifungal agents (P = 0.003) or insulin therapy (P = 0.041). Conclusions: Female COVID-19 patients with AKI, presenting with advanced disease and chest pain, having preexisting comorbidities, had increased mortality.